2019
DOI: 10.1053/j.gastro.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Lanreotide Reduces Liver Growth In Patients With Autosomal Dominant Polycystic Liver and Kidney Disease

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…Of these, four included ADPKD patients alone25–28 and the remaining two included patients with PLD and ADPKD, but provided a subset of data for ADPKD patients when measuring renal function and TKV 23 24. A further three publications were included as they were secondary analyses of previous studies,29–31 all of which were investigating the change in TLV for a subset of patients with PLD in a post-hoc analysis. Excluding patient numbers from secondary analysis, a total of 592 patients were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, four included ADPKD patients alone25–28 and the remaining two included patients with PLD and ADPKD, but provided a subset of data for ADPKD patients when measuring renal function and TKV 23 24. A further three publications were included as they were secondary analyses of previous studies,29–31 all of which were investigating the change in TLV for a subset of patients with PLD in a post-hoc analysis. Excluding patient numbers from secondary analysis, a total of 592 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Notable bias was detected in blinding for several studies. In ALADIN 2013 (and Pisani et al 30), physicians and staff were not blinded to patient allocation groups, and DIPAK-1 (and van Aerts et al 29) was an open-label study: therefore, both had a high risk of bias for blinding of participants. All studies except Ruggenentti et al 28 reported that TKV and TLV measurements were performed by blinded personnel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies did not observe any beneficial effect on the estimated glomerular filtration rate (eGFR) decline, but one trial documented that fewer patients progressed from chronic kidney disease stage 4 to stage 5 [27]. Similarly, lanreotide reduced both hepatic and renal cyst growth in ADPLD and ADPKD patients in several large studies [3,[28][29][30]. As total kidney volume (TKV) predicts disease progression in ADPKD, it was assumed that preventing renal cyst growth would also prevent eGFR decline [31].…”
Section: Somatostatin Analoguesmentioning
confidence: 99%